2018
DOI: 10.1002/ajhb.23195
|View full text |Cite
|
Sign up to set email alerts
|

Association of prepubertal obesity with pubertal development in Chinese girls and boys: A longitudinal study

Abstract: Objectives The purpose of this study was to examine the association of prepubertal body mass index (BMI) and weight status with pubertal development in boys and girls in Chongqing, China. Methods In a longitudinal study, 1237 students (695 boys and 542 girls) were recruited from Chongqing, China, and examined at baseline, then followed every 6 months for three and a half years. Height, weight, testicular volume, and breast development were measured at every examination. Age of first spermatorrhea and menarche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…According to results from studies reported in Table , girls with obesity enter puberty earlier compared with girls with normal weight . An explanation for the early onset of puberty in these girls might be found in the secretion of adipokines.…”
Section: The Onset Of Puberty In Girlsmentioning
confidence: 97%
See 4 more Smart Citations
“…According to results from studies reported in Table , girls with obesity enter puberty earlier compared with girls with normal weight . An explanation for the early onset of puberty in these girls might be found in the secretion of adipokines.…”
Section: The Onset Of Puberty In Girlsmentioning
confidence: 97%
“…The association between obesity and puberty onset in boys is rather controversial compared with findings in girls. Most studies reported an early onset of puberty in boys associated with increased BMI, while others reported no associations at all or a delayed onset of puberty (Table ) . The presence of excessive adipose tissue can be involved in puberty onset in boys as the secretion of adipokines can modulate both adrenarche and gonadarche.…”
Section: The Onset Of Puberty In Boysmentioning
confidence: 99%
See 3 more Smart Citations